Bilateral radiating osteoradionecrosis of the mandible after radioterapy in patients with nasopharyngeal carcinoma with unilateral fibular flap reconstruction - PENG Yongchun; DUAN Hongming; WU Hanjiang; ZHANG Sheng; FAN Tengfei (Kouqiang hemian waike zazhi)
[Objective:] To investigate the effect of fibular free flap on reconstruction of postoperative defects after radiation-induced bilateral osteoradionecrosis of the jaw (ORNJ). [Methods:] Seven patients with radiation ORNJ who were referrd to Department of Oral and Maxillofacial Surgery in our hospital from January 2010 to November 2020 were retrospected. Among the cases, 6 males and 1 female, aged 42 to 56 years old, were included. All patients had primary nasopharyngeal carcinoma, and recurrent nasopharyngeal carcinoma was excluded. Fibular free flap was used to reconstruct bilateral osteoradionecrosis of the mandible. The fibular osteotomy and tissue flap survival, complications in donor and recipient areas, and postoperative mouth opening were evaluated for reconstruction outcomes. [Results:] After 10 to 30 months of follow-up, free fibular composite flap was successfully used to reconstruct mandibular defects. Facial artery was selected in 5 cases, superior thyroid artery in 2 cases, and end-to-side anastomosis of internal jugular vein was performed in all recipient veins. One patient developed venous crisis 6 hours after surgery. Emergency surgical exploration revealed that the vein was twisted during end-to-side anastomosis and recovered well after re-anastomosis. The harvested fibula was 17.5-21.0 cm in length. No patient had serious donor or recipient site complications. All patients had satisfactory facial shape, remaining normal occlusion, and mouth opening was 2.5-3.3 cm. [Conclusion:] Fibular myocutaneous flap can reconstruct the bilateral mandibular soft and hard tissue defects after radiation in patients with ORNJ, which is worthy of clinical application.